Problematika Auditing Syariah Dalam Pelaksanaan Shariah Compliance di Lembaga Keuangan Syariah: Sebuah Meta-Sintesis - Ridwanto, Ridwanto; Abdullah, Muhammad Wahyuddin; Muchlis, Syaiful (Al-Sharf: Jurnal Ekonomi Islam, 2023)
Sharia financial institutions have a central role in the financial system based on the Sharia principles. Meanwhile, sharia audit as a monitoring tool has a crucial role in ensuring sharia compliance. In actualize their responsibilities, sharia auditors have several problems. This article aims to provide a more comprehensive brief insight into the problems of sharia auditing and offers practical solutions to increase compliance with Sharia values and principles in Indonesian sharia financial institutions. This article uses a meta-synthesis method to identify the main challenges in implementing sharia auditing in sharia financial institutions. The findings of the research results show that the primary challenges for sharia auditing in implementing sharia compliance are the lack of qualified sharia auditors, lack of sharia audit frameworks and standards, and also the lack of providing educational levels to the sharia supervisory board. The proposed solution involves enhancing the quality of auditors through training and certification, improving the sharia audit framework and standards, and also developing special education for the Sharia Supervisory Board.